Development of cognition decline in non-acute symptomatic patients with cerebral small vessel disease: Non-Acute Symptomatic Cerebral Ischemia Registration study (NASCIR)—rationale and protocol for a prospective multicentre observational study. Issue 2 (22nd February 2022) - Zhang, Shuting; Wang, Zhetao; Liu, Peng; Tuo, Qingzhang; Cheng, Yajun; Xu, Mangmang; Wu, Qian; Lei, Peng; Dai, Lunzhi; Kwapong, William Robert; Tan, Mingying; Liu, Ming
Abstract : Introduction: Headaches, dizziness and memory loss of unspecific causes are the most common non-acute ischemia symptoms in the ageing population, which are often associated with cerebral small vessel disease (CSVD) imaging markers; however, there is insufficient evidence concerning their association with the development of cognitive decline. This study aims to investigate risk factors, clinical course, cerebral and retinal imaging changes, proteomics features of non-symptomatic ischaemia symptomatic patients with cognitive decline. Methods and analysis: The Non-Acute Symptomatic Cerebral Ischemia Registration study is a multicentre, registry-based, prospective observational study, is designed to investigate the cognitive decline in non-acute ischaemia symptomatic patients. We will recruit 500 non-acute ischaemia symptomatic patients from four tertiary hospitals in China. For this study, non-acute ischaemia symptoms will be defined as headaches, dizziness and memory loss. Patients with headaches, dizziness or memory loss over 50 years of age will be included. Clinical features, cognitive assessment, cerebral and retinal imaging data, and a blood sample will be collected after recruitment. Patients will be followed up by structured telephone interviews at 1, 2, 3, 4, 5 years after recruitment. This study will improve our knowledge of the development of cognitive decline in non-acute ischaemia symptomatic patients and factors affecting the cognitive outcomes, which will eventually elucidate underlying pathways and mechanisms of cognitive decline in these patients and facilitate the optimisation of individualised interventions for its prevention and treatment. Ethics and dissemination: Ethics approval is obtained from The Biomedical Research Ethics Committee of West China Hospital, Sichuan University (Reference No. 2016 (335)). We will present our findings at national and international conferences and peer-reviewed journals in stroke and neurology. Trial registration number: ChiCTR-COC-17013056.